2012
DOI: 10.17221/72/2011-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Development of chemical soil properties in the western Ore Mts. (Czech Republic) 10 years after liming

Abstract: ABSTRACT:The article focuses on changes in soil chemistry observed on plots limed in 2000 in the western Ore Mts. (Krušné hory) on the basis of chemical analyses done before liming and repeated in 2002, 2005 and 2010. In the deeper mineral soil (down to 30 cm), only the increase in pH and exchangeable magnesium was significant. The increase in exchangeable calcium in upper soil layers was significant in 2002 and 2005 only; ten years after liming the effect was negligible, although the number of Ca deficient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In this sense, although not a study on liming, Leifeld et al (2013) have indeed provided evidence that higher C inputs to the soil due to greater aboveground productivity in alkaline soils can compensate for the observed faster soil carbon turnover in comparison to similar but acidic soils. The hypothesis of the progressive compensation of SOC losses is supported by the fact that the increments in SOC have been observed preferentially in the longest term studies (Šimek et al, 1999;Fornara et al, 2011), and that a progressive increment of SOC with time has also been observed within shorter studies (Srámek et al, 2012;Caires et al, 2006).…”
Section: F-valuementioning
confidence: 97%
See 2 more Smart Citations
“…In this sense, although not a study on liming, Leifeld et al (2013) have indeed provided evidence that higher C inputs to the soil due to greater aboveground productivity in alkaline soils can compensate for the observed faster soil carbon turnover in comparison to similar but acidic soils. The hypothesis of the progressive compensation of SOC losses is supported by the fact that the increments in SOC have been observed preferentially in the longest term studies (Šimek et al, 1999;Fornara et al, 2011), and that a progressive increment of SOC with time has also been observed within shorter studies (Srámek et al, 2012;Caires et al, 2006).…”
Section: F-valuementioning
confidence: 97%
“…Srámek et al (2012) reported that liming increased SOC concentrations in forest soils (mainly Podzols and Gleysols) in Sweden, the first 10 years after liming, from initial values of 108 g C kg À1 to 143 g C kg À1 in the upper 2 cm, and from 39 g C kg À1 to 51 g C kg À1 in the 2-30 cm section. Poulton et al (2003) studied C sequestration in trees and soil in the Geescroft and Broadbalk Wildernesses sites, two woodland areas formed on abandoned arable land 130 years ago, one of which (Broadbalk) had been treated with chalk before abandonment.…”
Section: Effect On Forest Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values characterise a low supply level of magnesium. That the effect of liming on the mineral horizons can be anticipated with a certain delay was confirmed in respect of the Krušné hory Mts., and also for other forest regions (Podrázský 2006;Šrámek et al 2012).…”
Section: Changes In the Soil Chemistrymentioning
confidence: 99%
“…The study of anthropogenic influence on soils is an actual necessity of our times. In order to improve the methods of soil fertility conservation, control and forecast changes in arable soils, the necessity to study the regular patterns of changes in basic properties of agricultural soil is recognized [1][2][3]. The problem of the fertility reduction in acidic soils in various regions of the world has been recognized for a long period of time [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%